Polish Policy and Its Image in the Period 2015–2018 as Seen by Two Journalists of the “Polityka” Weekly – Mariusz Janicki and Wiesław Władyka - Anculewicz, Zbigniew (Media - Culture - Social Communication, 2020)
This analysis is based on all articles published in the printed version of the “Polityka” weekly between 2015 and 2018, i.e. from the beginning of the presidential campaign in the early spring of 2015 until the results of the local elections in 2018, written by Mariusz Janicki and Wiesław Władyka. They also referred to the vision of the presidency that the newly-elected President of the Republic of Poland, Andrzej Duda, decided to implement. However, these renowned observers of the Polish political scene devoted most of their attention to the peculiar “Polish-Polish” war of “two tribes” – the war between the “PiS camp” and the “anti-PiS camp.” The principal methodology adopted in this paper is an analysis of the journalistic sources in juxtaposition with the latest scientific studies devoted to the transformation of Polish policy and changes occurring in Polish society at the end of the second decade of the 21st century. The dedicated journalism of Janicki and Władyka, who do not conceal their political sympathies and antipathies, constitutes a new type of journalism that is becoming more common not only in Poland but also in the United States. It is also one of the most evident symptoms showing that objectiveand critical journalism from the position of an observer of the political scene, rather than active involvement on one side of a political dispute, is right now passing into history.